1985
DOI: 10.1007/bf01570849
|View full text |Cite
|
Sign up to set email alerts
|

The classification of complications after augmentation rhinoplasty

Abstract: The authors classify the complications resulting from augmentation rhinoplasty into 6 types according to the nasal areas involved, then guide the reader to the corresponding technique of management for each type. Their classification is based on the data of 113 patients whom they treated with a secondary rhinoplasty in their clinic during the past 10 years. In the case of augmented noses, it is especially noted that removal of the implant must precede any further treatment in a secondary rhinoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…[15][16][17] They are mostly due to overcorrection or high pressure of the overlying skin. 4,18 As of yet, these complications have still not been experienced with our footplate incision procedure, though the follow-up time may not have been sufficient. When simultaneous alar base augmentation is required for the correction of the retracted alar base, cartilage or an implant can be inserted into the alar base pocket through this incision, without making any additional incision necessary.…”
Section: Discussionmentioning
confidence: 71%
“…[15][16][17] They are mostly due to overcorrection or high pressure of the overlying skin. 4,18 As of yet, these complications have still not been experienced with our footplate incision procedure, though the follow-up time may not have been sufficient. When simultaneous alar base augmentation is required for the correction of the retracted alar base, cartilage or an implant can be inserted into the alar base pocket through this incision, without making any additional incision necessary.…”
Section: Discussionmentioning
confidence: 71%
“…Nevertheless, potential complications, such as infection, extrusion, contraction, and delayed inflammation, lead to preferences for autologous materials over silicone [ 10 ]. The risk of complications after augmentation rhinoplasty with silicone implants has been reported to vary greatly from study to study, from 4% to 24% [ 8 9 11 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Complications related to silicone implants, such as discoloration, dislocation, extrusion, contraction resulting from a foreign body reaction, and infection have been reported [ 12 ]. Among the major complications requiring either removal or revision of the prosthesis, only 2.5% occurred early, within 30 days of the procedure [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…29 Two studies looking at 1000 and 2500 cases of Asian rhinoplasty found a combined infection/ extrusion rate as low as 0.48 percent. 30,31 The dorsal nasal skin in Asian patients tends to be thicker than in Caucasian noses, which may provide better soft-tissue pockets, thereby allowing improved support of a Silastic framework with lower overall complication profiles. 32 It has been suggested that higher rates of extrusion may be related more to lack of surgeon experience and implant design.…”
Section: Siliconementioning
confidence: 99%